Fcγ-receptor-IIIA bioactivity of circulating and synovial immune complexes in rheumatoid arthritis - Hanns-Martin Lorenz; Norbert Blank; Wolfgang Merkt; Philipp Kolb; Lea Rodon; Ivana Andreeva (RMD Open)
Objective Previous technical limitations prevented the proof of Fcγ-receptor (FcγR)-activation by soluble immune complexes (sICs) in patients. FcγRIIIa (CD16) is a risk factor in rheumatoid arthritis (RA). We aimed at determining the presence of CD16-activating sICs in RA and control diseases.Methods Sera from an exploratory cohort (n=50 patients with RA) and a validation cohort (n=106 patients with RA, 20 patients with psoriasis arthritis (PsA), 22 patients with systemic lupus erythematosus (SLE) and 31 healthy controls) were analysed using a new reporter cell assay. Additionally, 26 synovial fluid samples were analysed, including paired serum/synovial samples.Results For the first time using a reliable and sensitive functional assay, the presence of sICs in RA sera was confirmed. sICs possess an intrinsic capacity to activate CD16 and can be found in both synovial fluid and in blood. In low experimental dilutions, circulating sICs were also detected in a subset of healthy people and in PsA. However, we report a significantly increased frequency of bioactive circulating sICs in RA. While the bioactivity of circulating sICs was low and did not correlate with clinical parameters, synovial sICs were highly bioactive and correlated with serum autoantibody levels. Receiver operator curves indicated that sICs bioactivity in synovial fluid could be used to discriminate immune complex-associated arthritis from non-associated forms. Finally, circulating sICs were more frequently found in SLE than in RA. The degree of CD16 bioactivity showed strong donor-dependent differences, especially in SLE.Conclusions RA is characterised by the presence of circulating and synovial sICs that can engage and activate CD16.